Developing a Core Outcome Set for Clinical Trials of Chinese Medicine for Hyperlipidemia - Li, Geng; Han, Ruxue; Lin, Mingjun; Wen, Zehuai; Chen, Xiankun (Frontiers in Pharmacology, 2022)
Background: Chinese medicine (CM) is widely used, and has been proven effective, for treating hyperlipidemias in China. However, the heterogeneity of outcomes measured and reported across trials exacerbates the obstacles of CM evidence synthesis and effectiveness comparison. Developing a core outcome set (COS) would resolve these issues. In this study, we develop a COS for CM clinical trials for hyperlipidemia (COS-CM-Hyperlipidemia) in order to tackle the outcome issues. Methods: We generated candidate outcomes through a systematic review of interventional and observational studies of Chinese medicine for hyperlipidemias. This was followed by a three-round Delphi survey. The stakeholders were hyperlipidemia patients, clinicians or researchers, in either CM/integrated Chinese or Western medicine, clinical pharmacy, clinical epidemiology or statisticians, or editors of important relevant journals and an ethicist. They used a 9-point Likert scale to determine how important they felt each outcome was in determining treatment success. A consensus meeting was held to confirm the final COS, based on the Delphi survey results. Results: We identified a total of 433 outcomes from 3,547 articles, and 28 outcomes from 367 registered trials. After standardization, we selected 71 outcomes to develop a preliminary outcome list for further consensus. After three Delphi survey rounds and one consensus meeting, the most important outcomes were determined for COS-CM-Hyperlipidemia. It included cardiovascular events, low-density lipoprotein cholesterol, risk of cardiovascular disease, total cholesterol, carotid intima-media thickness, high-density lipoprotein cholesterol, triglycerides, cerebrovascular events, adverse drug reactions and patient-reported symptoms. Conclusion: Though there are several limitations to this research, such as the stakeholders’ limited geographical representation and the lack of recommended outcome measurement instruments, COS-CM-Hyperlipidemia may improve outcome reporting consistency in clinical trials. Further work is needed to explore the optimal methods for measuring these outcomes. Registration: The Core Outcome Measures in Effectiveness Trials Initiative (COMET): http://www.cometinitiative.org/studies/details/983. Registered on 25 April 2017.